Factors influencing the decision to study a master’s degree at Binh Duong University - Pham, Hồng Nhung; Cao , Thị Việt Hương (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
The study was conducted to identify factors affecting the decision to study a master’s program at Binh Duong University, thereby providing management suggestions to improve the quality of training, services and increase the decision to study a master’s degree at the university. The results showed that there are 6 factors affecting the decision to study a master’s degree at Binh Duong University with decreasing levels: (1) Subjective standards; (2) Training quality; (3) Tuition and tuition policies; (4) Career opportunities; (5) Communication; (6) University reputation.